Open and closed mode of online discussion - does it matter? - Abd. Jalil, Habibah; McFarlane, Angela (Universiti Putra Malaysia Press, 2010)

(untitled)
This paper addresses some issues concerning online task type. Using categories, namely, Scaffolding, Feedback on Performance, Cognitive Structuring, Modelling, Contingency Management, Instructing and Questioning to analyze message transactions, or means of assistance in CMC ‘Discussion Board’, this study involved a total of 48 participants consisting of 36 students and 12 tutors in a Masters programme. Here, the CMC was used as a communication tool, extending face-to-face (or classroom) discussion. CMC was used in an adjunct mode. It was found that open tasks are more likely to generate more open modes of discussion. When there is ‘assistance seeking’, ‘assistance giving’ should always follow. In addition, open mode discussions also seemed to offer the students more opportunities to raise their concerns about their learning compared to the closed mode. Using these findings, a simple approach to distinguish discussion modes is proposed.